PENDUGAAN PRODUKSI JERNANG (Daemonorops didymophylla Becc.) BERDASARKAN KARAKTERISTIK MORFOMETRIK ROTAN - Rina Wulan Sari; Agus Hikmat; Yanto Santosa (Media Konservasi, 2015)
Dragon’s blood is pure powder that resulted from extraction of rattan fruit skin of genus Daemonorops. This study aimed to determine the morphometric variables were correlated with the production of rattan dragon’s blood and to formulate a mathematical model to predict the production of dragon’s blood according to correlate variables. This research was conducted in the village of Bukit Mangkekal Gedung Sako  Kaur District Bengkulu Province and 35 samples were used by measuring the rattan clumps morphometric parameters (length of rattan stems, diameter of stem, and number of panicles) at 43 rattan sticks. The results of statistical analysis (multiple linear regression with stepwise method) the correlation between the average length of bunches weight pure powder obtained regression equation for pure powder weight Y= -0.251 + 0.087x. (R2=0.873). Morphologically size in this case was the average length of bunches generative growth are easily observable and was a parameter determining the amount of fruit and pure powder produced from rattan stick. Morphometric parameters used were part of the plant that is easy to take measurements and an important part in determining the production of fruit and a pure powder using morphometric methods. Keyword: Dragon’s blood, morphometric, production model